Supine Percutaneous Nephrolithotomy, Is It Really Effective? A Systematic Review of Literature - Basiri, Abbas; Mohammadi Sichani, Mehrdad (Urology Journal, 2009)
Introduction: This systematic review was performed to determine the clinical value of percutaneous nephrolithotomy in the supine position in comparison with the convention of performing the procedure in the prone position. Materials and Methods: A systematic review of the medical literature was conducted searching for studies on percutaneous nephrolithotomy in the supine position, limited to publications appeared in the PubMed between 1980 and July 2008. Non-English articles were considered if deemed relevant by providing additional data. In the retrieved articles, reference lists were hand-searched to identify additional relevant articles. Results: There were 9 original articles on percutaneous nephrolithotomy in the supine position. Five studies were retrospective and 4 were prospective, of which only 1 was a well-designed randomized controlled trial published in 2008. The success rate of the procedure was reported between 69.6% and 95%. The risk of requiring blood transfusion was between zero and 8%. Duration of hospital stay was variable, but generally less than that in the prone position. No colon perforation was reported. Conclusion: In carefully selected patients with uncomplicated urinary calculi, percutaneous calculus removal in the supine position can yield similar outcomes to that in the prone position.